An observational study of stroke synchronisation in crew-boat sprint kayaking - Tay, C. S.; Kong, P. W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The four-seater K4 is the largest crew-boat in Olympic sprint kayaking. Four paddlers work in unison to propel their boat over distances of 200-, 500- or 1000-m in the shortest time. The role of stroke synchronisation in successful crew-boat performance has been debated; some think that perfect synchronisation is essential (e.g. Wing and Woodburn, 1995), while others think a slight asynchronicity in the blade movement is important (de Brouwer et al., 2013). The aim of this study was to identify the extent of stroke synchronisation for a K4 200-m crew. Methods: High-speed (120 Hz) video of a men`s K4 200-m crew from a national team was recorded from the sagittal view during a selection timetrial. Video analysis was performed to identify the stroke positions (catch, immersion, extraction and release) of each paddler in the K4, based on McDonnell and colleagues` model (2012). An offset variable, defined as the timing difference between a paddler compared to the first-seat paddler, was obtained for each paddler. The offset was interpreted as either negative, zero, or positive e.g. a negative offset occurs when the back paddler catches before the 1st seat paddler. For all offset variables, mean and 95% CI was calculated. Results: The performance timing was 31.87 s. A total of 41 strokes (excluding the first 3 acceleration strokes) were analysed. The mean absolute offset was 90 [79, 100] ms. At the specific stroke positions, the values were: catch 89 [79, 94] ms, immersion 71 [65, 78] ms, extraction 104 [90, 119] ms and release 96 [86, 107] ms. By paddler position, the offsets were: 2nd seat 39 [34, 45] ms, 3rd seat 4 [-1, 9] ms and 4th seat 16 [8, 24] ms. Discussion: The results show a tendency for positive-offset synchronisation patterns for the crew, where the 2nd, 3rd, and 4th seat paddlers are slower than the 1st seat paddler. The crew was more synchronised at the immersion position, and least synchronised at the release position. This adds a new perspective to the crew-boat stroke synchronisation theories, that perhaps it is important to be synchronised at one part of the stroke but slightly asynchronised at the other positions. Interestingly, it was the 2nd seat paddler that was most out-of-sync to the 1st seat paddler despite being the closest and having the best view to follow the 1st seat paddler`s movements. This highlights the need for future studies to uncover the mechanisms of how synchronisation is achieved. Besides Olympic sprint kayaking, such information would also be useful for other similar sports with crew-boat racing like rowing and dragon boat racing.